Exploring the pharmacy students’ perspectives on off-campus online learning experiences amid COVID-19 crises: A cross-sectional survey - Asim Ahmed Elnour; Abdalla Abou Hajal; Rola Goaddar; Nada Elsharkawy; Samar Mousa; Nour Dabbagh; Mariam Mohamad Al Qahtani; Sara Al Balooshi; Nosayba Othman Al Damook; Adel Sadeq (Saudi Pharmaceutical Journal, 2023)
Background: The pandemic of COVID-19 has placed many challenges for pharmacy students’ learning experiences via the online e- system. There is paucity of studies that addresses this in colleges of pharmacies in United Arab Emirates (UAE). Objective: We have explored the preparedness, attitudes, experiences, and barriers/facilitators, and delineated factors that may affect the pharmacy students’ e-learning process amid the COVID-19 crises. Methods: The current study was cross-sectional, and survey-based (anonymously self-administered) that utilized theoretical domains framework. The survey (multiple statements) was comprised of four domains (based on theoretical domain framework) that has elaborated on the preparedness, attitudes, experiences and barriers for the pharmacy students’ e-learning (all years and interns). The validated (Cronbach Alfa 0.821) and piloted survey posted to the Google form and a link distributed to the pharmacy students. The survey was comprised of four domains (34 statements), distributed as five in preparedness, eleven in attitude, eleven in the experiences, and seven in the barriers/facilitators (theoretical domains framework). Outcome measure: The primary outcome was the total sum of scores of individual statements and each individual four domain of the questionnaire (preparedness, attitude, experiences, and barriers/facilitators). Results: Two hundred thirty respondents participated in the survey (230/400, response rate 57.5%), of which 193 were females (83.9%) versus 37 males (16.1%). The mean age (years) was 19.9 ± 1.9 (males 19.8 ± 1.6 and females 20.0 ± 1.9). The mean total score for preparedness Q1 to Q5 (domain maximum score 25); and for the attitude Q6 to Q16 (domain maximum score of 60) were 14.9 ± 3.8 (95% CI 14.4 – 15.4; P < 0.05), 29.5 ± 7.4 (95% CI 28.6 – 30.5; P < 0.05) respectively. While for the experiences Q17 to Q27 (domain maximum score 55); and for the barriers/facilitators Q28 to Q34 (domain maximum score 30) 40.1 ± 8.0 (95% CI 39.1 – 41.1; P < 0.0001), and 20.9 ± 4.9 (95% CI 20.3–21.5;P < 0.05) respectively. Conclusion: Our pharmacy students support the use of e-learning in pharmacy education, and seems prepared for the future technology moves in education. The colleges of pharmacies need to conduct further research on versatile innovative models such as virtual learning/artificial intelligence that fits with their students’ perspectives.